Presence of heavy metals in organic cacao (theobroma cacao l.) crop (2012)
The presence of heavy metals in cocoas crop is becoming a problem for farmers and cooperatives at Huánuco and Ucayali regions, Peru. In this research cadmium and lead contents in cocoa soils and leaves were evaluated. For it, soil and foliar samples were collected in 22 organic crop plots located at Huánuco (17) and Ucayali (5) regions. Pearson correlation analysis was performed between available content of lead and cadmium in soils with foliar variables (P, Mg, Ca, Zn, Cd, Pb) and soil (Sand, Clay and K) variables. According to the soil analysis only the potassium was deficient; while in leaf tissue deficiencies of N, P, K, Mg and Zn were observed. The average values of available cadmium and lead in soils were 0.53 ppm and 3.02 ppm and in leaves were 0.21 ppm and 0.58 ppm respectively.